2016
DOI: 10.4238/gmr.15027516
|View full text |Cite
|
Sign up to set email alerts
|

Association between the pre-miR-196a2 rs11614913 polymorphism and gastric cancer susceptibility in a Chinese population

Abstract: ABSTRACT. We did a case-control study to provide a more comprehensive evaluation of the association of the pre-miR-196a2 rs11614913 polymorphism with gastric cancer. Between January 2013 and December 2014, 182 patients newly diagnosed with primary gastric cancer and 182 control subjects were recruited at Zhengzhou People's Hospital. For SNP genotyping, we used the Assay Designer 3.1 to design the primers of polymerase chain reaction. Using the chisquare test, we found that patients with gastric cancer were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…However, these findings seem to agree with previous studies stating that alterations in pre-miRNAs could affect the expression levels of genes involved in oncogenesis. The association trend between pre-mir34a rs72631823 and TNBC is in accordance with the studies of Morales S et al [25] and Li M et al [26] that present the association of single nucleotide polymorphisms in pre-miRNAs with breast cancer in a South American population and gastric cancer in a Chinese population. Pre-miRNA polymorphisms seem to affect oncogenesis by modifying the cellular levels of mature miRNA, as it is mentioned in the study of Lv H and his colleges [21].…”
Section: Discussionsupporting
confidence: 91%
“…However, these findings seem to agree with previous studies stating that alterations in pre-miRNAs could affect the expression levels of genes involved in oncogenesis. The association trend between pre-mir34a rs72631823 and TNBC is in accordance with the studies of Morales S et al [25] and Li M et al [26] that present the association of single nucleotide polymorphisms in pre-miRNAs with breast cancer in a South American population and gastric cancer in a Chinese population. Pre-miRNA polymorphisms seem to affect oncogenesis by modifying the cellular levels of mature miRNA, as it is mentioned in the study of Lv H and his colleges [21].…”
Section: Discussionsupporting
confidence: 91%
“…[9][10][11] MiR-196a2 is an important member of the miRNA-196 precursor family found in the homeobox (HOX) clusters region of the human genome. 12 An extensively studied miR-196a2 variant is rs11614913 (C > T), which is investigated in a plethora of cancers, including breast cancer, [13][14][15][16][17] gastric cancer, [18][19][20][21][22] hepatocellular carcinoma, [23][24][25] colorectal cancer, [26][27][28][29] lung cancer, [30][31][32] gynecological cancer, [33][34][35][36][37][38] prostate cancer, [39][40][41] and so on. Despite a large number of studies performed in almost all ethnic populations, the contribution of rs11614913 polymorphism to cancer risk is still inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with CC genotype, CT genotype carriers had an increased risk of GPL and GC. Similarly, Li et al (2016) found an association between miR-196a2 rs11614913 and elevated GC risk. In addition, we identified that CT genotype and C allele of miR-27a rs895819 were associated with a higher risk of GC.…”
Section: Discussionmentioning
confidence: 86%